Collaboration Between Actors in the Management of Colorful Jodipan Village Tourism in Malang City - Nadia Muslimatul Ummah; Karina Dian Pitaloka; Rafif Dhia Pratama; Kartika Putri Maharani; Muhammad Albana; Prisca Kiki Wulandari (Cv. Kayaswara, Indonesia, 2025)
Jodipan Colorful Village (KWJ) is one of the community-based tourism destinations managed by the Malang City Government through cross-sectoral collaboration. This tourist destination serves as an interesting example of how collaboration among various actors can play a role in transforming residential areas into city tourism icons. This article aims to examine the forms, dynamics, and effectiveness of inter-actor collaboration in the management of KWJ, focusing on the roles of the Malang City Office of Youth, Sports, and Tourism, the Jodipan Urban Village Tourism Awareness Group (Pokdarwis), as well as the involvement of local communities and private sector partners. This research employs a descriptive qualitative method through a case study approach, using data collection techniques such as in-depth interviews, field observations, and policy document reviews. The study analyzes the collaborative tourism management using the analytical framework of Governance Network Theory proposed by Klijn and Koppenjan (2012). The results show that the collaboration among actors in KWJ has been formed in a collaborative yet informal manner, with an imbalanced distribution of roles, as local communities and residents have predominantly been the main driving force in managing the tourism area.